2008
DOI: 10.1515/hf.2008.029
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of thermo-hygro-mechanically (THM)-densified wood by soft-rot fungi

Abstract: Thermo-hygro-mechanical (THM)-densified wood is more resistant to colonisation and degradation by brown-rot fungi than untreated wood. Colonisation and degradation by soft-rot fungi was investigated in treated Norway spruce (Picea abies) and treated beech (Fagus sylvatica) to assess their suitability for utility class 4. Three different treatments were applied: thermal-hygro (TH) treatment, mechanical densification and THM-treatment including densification and post-treatment under saturated steam conditions at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In a previous study on the soft rot resistance of THMdensified wood, Skyba et al (2008) recorded a pronounced effect of THM treatment in the outer wood surface that suppressed colonisation and degradation of inner regions of the wood samples during incubation. The same phenomenon was observed in the present study in which hyphae were not detected in deeper regions of the wood and cell wall degradation was restricted to the outer surfaces of THM-densified wood.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a previous study on the soft rot resistance of THMdensified wood, Skyba et al (2008) recorded a pronounced effect of THM treatment in the outer wood surface that suppressed colonisation and degradation of inner regions of the wood samples during incubation. The same phenomenon was observed in the present study in which hyphae were not detected in deeper regions of the wood and cell wall degradation was restricted to the outer surfaces of THM-densified wood.…”
Section: Discussionmentioning
confidence: 89%
“…However, studies of the resistance of THM-densified beech and Norway spruce wood to soft rot fungi revealed that both types of wood are highly susceptible and therefore inappropriate for use in utility class 4, i.e., in contact with ground or fresh water (Skyba et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Because of these superior characteristics, wood is popular and widely used in many areas. However, under suitable climatic conditions, wood is easily biodegradable and vulnerable to various organisms like fungi and insects [1,2]. Wood contains cellulose, hemicellulose, lignin, and small amounts of sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature treatments at 160-2008C decrease the hydrophility of wood and improves its bio-durability. Thermohygromechanically treated wood has similarly improved properties (Skyba et al 2008(Skyba et al , 2009. Disadvantages are the loss of mechanical strengths (Biziks et al 2010) and the considerable energy input.…”
Section: Introductionmentioning
confidence: 99%